2018
DOI: 10.1002/jcp.27368
|View full text |Cite
|
Sign up to set email alerts
|

Stromal vascular fraction cells plus sustained release VEGF/Ang‐1‐PLGA microspheres improve fat graft survival in mice

Abstract: Autologous fat transplantation is increasingly applied in plastic and reconstructive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Previous research found that stromal vascular fraction cells (SVFs) could improve fat graft survival in mice 28 . As an important component of SVFs, ADSCs appear to be pure and effective for co‐transplantation with fat grafts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research found that stromal vascular fraction cells (SVFs) could improve fat graft survival in mice 28 . As an important component of SVFs, ADSCs appear to be pure and effective for co‐transplantation with fat grafts.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the key factors in the differentiation of ADSCs into pericytes, the interaction of HUVECs and Previous research found that stromal vascular fraction cells (SVFs) could improve fat graft survival in mice. 28 As an important component of SVFs, ADSCs appear to be pure and effective for co-transplantation with fat grafts. The present study developed a new aspect of promoting vascularization in fat grafting by regulating miR-24-3p in ADSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The slow vascular regeneration process suppressed the lipolysis and β-oxidation of fatty acids, and resulted in the formation of oil cysts. Conversely, decreased oil cysts were observed in fat grafts assisted by stromal vascular fraction cells or vascular endothelial growth factor (VEGF) ( Lu et al, 2009 ; He et al, 2019 ). Simultaneously, macrophages act as major immune cells in promoting angiogenesis and vascular regeneration ( Godwin et al, 2013 ; Godwin et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have attempted to solve the abovementioned problems by improving the blood supply or increasing adipose stem cells. For example, stromal vascular components (SVFs) [21], cell-assisted fat transplantation [22] and cytokines have been used [23]. Although substantial progress has been made, many complications persist, and the cumbersome operation is also a hindrance.…”
Section: Discussionmentioning
confidence: 99%